Targeted delivery of silibinin via magnetic niosomal nanoparticles: potential application in treatment of colon cancer cells - Shafiei, Golchin; Jafari-Gharabaghlou, Davoud; Farhoudi-Sefidan-Jadid, Mahdi; Alizadeh, Effat; Fathi, Marziyeh; Zarghami, Nosratollah (Frontiers in Pharmacology, 2023)
In recent years, various nanoparticles (NPs) have been discovered and synthesized for the targeted therapy of cancer cells. Targeted delivery increases the local concentration of therapeutics and minimizes side effects. Therefore, NPs-mediated targeted drug delivery systems have become a promising approach for the treatment of various cancers. As a result, in the current study, we aimed to design silibinin-loaded magnetic niosomes nanoparticles (MNNPs) and investigate their cytotoxicity property in colorectal cancer cell treatment. For this purpose, MNPs ferrofluids were prepared and encapsulated into niosomes (NIOs) by the thin film hydration method. Afterward, the morphology, size, and chemical structure of the synthesized MNNPs were evaluated using the TEM, DLS, and FT-IR techniques, respectively. The distribution number of MNNPs was obtained at about 50 nm and 70 nm with a surface charge of -19.0 mV by TEM and DLS analysis, respectively. Silibinin loading efficiency in NIOs was about 90 %, and the drug release pattern showed a controlled release with a maximum amount of about 49 % and 70%, within 4 h in pH=7.4 and pH=5.8, respectively. To investigate the cytotoxicity effect, HT-29 cells were treated with the various concentration of the drugs for 24 and 48 h and evaluated by the MTT as well as flow cytometry assays. Obtained results demonstrated promoted cell cytotoxicity of silibinin-loaded MNNPs (5-fold decrease in cell viability) compared to pure silibinin (3-fold decrease in cell viability) while had no significant cytotoxic effect on HEK-293 (normal cell line) cells, and the cellular uptake level of MNNPs by the HT-29 cell line was enhanced compared to the control group. In conclusion, silibinin-loaded MNNPs complex can be considered as an efficient treatment approach for colorectal cancer cells.